miR-107 Inhibits the Proliferation of Gastric Cancer Cells In vivo and In vitro by Targeting TRIAP1 - Yan, Jiexin; Dai, Lu; Yuan, Jun; Pang, Min; Wang, Yueqiu; Lin, Lang; Shi, Yawei; Wu, Fuli; Nie, Rongping; Chen, Qiuling; Wang, Lei (Frontiers in Genetics, 2022)
Gastric cancer is a kind of gastrointestinal tumor with high morbidity and mortality. Finding effective methods for early diagnosis and treatment of gastric cancer has important significance and application prospects. MicroRNAs without protein coding potential affect the occurrence and development of gastric cancer. This study aims to explore the biological function and mechanism of microRNA-107 (miR-107) in gastric cancer. The results show that miR-107 is low expressed in gastric cancer, while TRIAP1 is highly expressed; the overexpression of miR-107 can inhibit the progression of gastric cancer in vivo and in vitro, while the overexpression plasmid of TRIAP1 can restore the miR-107 mimic-induced cell proliferation and metastasis inhibition, and the small interfering RNA of TRIAP1 can inhibit the cell proliferation and invasion induced by miR-107 inhibitor. In conclusion, the results of this study show that miR-107 can inhibit the proliferation of gastric cancer in vivo and in vitro by targeting TRIAP1.